Repurposing Approach Identifies Auranofin with Broad Spectrum Antifungal Activity That Targets Mia40-Erv1 Pathway - Thangamani, Shankar; Maland, Matthew; Mohammad, Haroon; Pascuzzi, Pete E.; Avramova, Larisa; Koehler, Carla M.; Hazbun, Tony R.; Seleem, Mohamed N. (Frontiers in Cellular and Infection Microbiology, 2017)
Current antifungal therapies have limited effectiveness in treating invasive fungal infections. Furthermore, the development of new antifungal is currently unable to keep pace with the urgent demand for safe and effective new drugs. Auranofin, an FDA-approved drug for the treatment of rheumatoid arthritis, inhibits growth of a diverse array of clinical isolates of fungi and represents a new antifungal agent with a previously unexploited mechanism of action. In addition to auranofin's potent antifungal activity against planktonic fungi, this drug significantly reduces the metabolic activity of Candida cells encased in a biofilm. Unbiased chemogenomic profiling, using heterozygous S. cerevisiae deletion strains, combined with growth assays revealed three probable targets for auranofin's antifungal activity—mia40, acn9, and coa4. Mia40 is of particular interest given its essential role in oxidation of cysteine rich proteins imported into the mitochondria. Biochemical analysis confirmed auranofin targets the Mia40-Erv1 pathway as the drug inhibited Mia40 from interacting with its substrate, Cmc1, in a dose-dependent manner similar to the control, MB-7. Furthermore, yeast mitochondria overexpressing Erv1 were shown to exhibit resistance to auranofin as an increase in Cmc1 import was observed compared to wild-type yeast. Further in vivo antifungal activity of auranofin was examined in a Caenorhabditis elegans animal model of Cryptococcus neoformans infection. Auranofin significantly reduced the fungal load in infected C. elegans. Collectively, the present study provides valuable evidence that auranofin has significant promise to be repurposed as a novel antifungal agent and may offer a safe, effective, and quick supplement to current approaches for treating fungal infections.